The Philosophical Function of Contracts in Realizing Justice - Niru Anita Sinaga (CV. Strata Persada Academia, 2023)
This research aims to determine and discuss the philosophical function of a contract to realize justice. Therefore, what things must be fulfilled so that the philosophical function of the contract in realizing justice for the parties can be carried out is also included in the objectives of this research. This type of research is normative juridical research, using secondary data obtained from primary, secondary and tertiary legal material sources. The results of this research reveal that contracts have a fundamental philosophical function, namely realizing the value of justice in the social and economic order in society by facilitating, accommodating and regulating the contractual legal relationships of the parties in which there are balanced rights and obligations. In other words, contracts also function as legal instruments to eliminate or at least reduce imbalances in the social and economic order in society, especially in contracts made by parties as citizens or part of society.